Pembangkit Listrik Tenaga Surya Dan Penerapannya Untuk Daerah Terpencil - Kholid Akhmad (Jenderal Soedirman University, 2005)
Solar cell is a device which is capable of converting directly the energy of light to electricity. This device have been implemented in some rural areas of Indonesia as solar home systems of 50 Wp, and PV-diesel hybrid systems. While operation, the solar cell system didn¶ t need fossil fuel, no result pollution and noise to the environment, almost maintenance free, and very easy to operate. The solar radiation is the renewable energy source of solar cell which is abundance and unlimited. However, the solar cell is the promising one as a future energy technology of Indonesia.